Lizard polymorphic throat colors are distinguishable by conspecifics and predators across variable light environments - Graham T. BeVier; Kinsey M. Brock (PLoS ONE, 2025)
Color polymorphisms, or distinct color variants within a population, provide tractable study systems for studying the generation, maintenance, and loss of phenotypic diversity in nature because biologists can easily observe changes in the number and frequency of discrete variants over time. However, many color polymorphisms are studied in the context of the human visual system and do not consider how conspecifics or potential predators view morph variation. The visual systems of predators and conspecifics may be sensitive to different aspects of coloration, which can influence the evolution and maintenance of morph diversity and phenotypic variation within and between populations. The Aegean wall lizard (Podarcis erhardii) is a color polymorphic lizard that exhibits co-occurring orange, white, and yellow throat color morphs. Here, we measured the reflectance of P. erhardii throat color patches and used visual modelling to determine if lizards and their bird and snake predators can visually discriminate between morph colors across different lighting contexts. Our results suggest that P. erhardii and their violet-sensitive bird and snake predators can distinguish chromatically between each color morph pair in standard daylight and forest shade illuminance contexts. However, only P. erhardii can distinguish achromatic morph colors in both illuminance contexts (except for white and yellow morphs in forest shade). These results indicate that P. erhardii morphs are most difficult for predators to distinguish in low lighting conditions and could help explain previously observed morph differences in microhabitat usage.